On creativity - Bohm, David (London ; New York : Routledge, 2004)
Creativity is fundamental to human experience. In On Creativity David Bohm, the world-renowned scientist, investigates the phenomenon from all sides: not only the creativity of invention and of imagination but also that of perception and of discovery. This is a remarkable and life-affirming book by one of the most far-sighted thinkers of modern times.
1. On creativity ; 2. On the relationships of science and art ; 3. The range of imagination ; 4. The art of perceiving movement ; 5. Art, dialogue, and the implicate order.
Str. [146]: Bibliografija. - Kazalo.
Keywords: umjetnička kreacija; umjetnost i znanost; kreativne mogućnosti u znanosti; kreacija u umjetnosti